2014
DOI: 10.1113/expphysiol.2014.082867
|View full text |Cite
|
Sign up to set email alerts
|

Slower lower limb blood pooling in young women with orthostatic intolerance

Abstract: New Findings r What is the central question of this study?Orthostatic stress is mostly caused by venous blood pooling in the lower limbs. Venous distension elicits sympathetic responses, and increased distension speed enhances the cardiovascular response. We examine whether lower limb blood pooling rate during lower body negative pressure is linked to orthostatic intolerance. r What is the main finding and its importance?A similar amount of blood was pooled in the lower limb, but at a slower rate in women who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Although the time to develop 50% of the capacitance response (poolingtime) was similar in controls and VVS, the groups presented with dichotomous correlation between poolingtime and LBNP-induced cardiovascular responses as well as orthostatic tolerance. A recent study found that the time for lower limb blood pooling was much shorter in hemodynamic stable healthy women compared to otherwise healthy women experiencing vasovagal reactions during moderate levels of LBNP (77). In corroboration, we found that shorter poolingtime correlated with higher LBNP-tolerance in healthy controls ( figure 16A).…”
Section: Effects Of Blood Pooling Time On Lbnp Tolerancesupporting
confidence: 89%
See 4 more Smart Citations
“…Although the time to develop 50% of the capacitance response (poolingtime) was similar in controls and VVS, the groups presented with dichotomous correlation between poolingtime and LBNP-induced cardiovascular responses as well as orthostatic tolerance. A recent study found that the time for lower limb blood pooling was much shorter in hemodynamic stable healthy women compared to otherwise healthy women experiencing vasovagal reactions during moderate levels of LBNP (77). In corroboration, we found that shorter poolingtime correlated with higher LBNP-tolerance in healthy controls ( figure 16A).…”
Section: Effects Of Blood Pooling Time On Lbnp Tolerancesupporting
confidence: 89%
“…Furthermore, studies in healthy subjects without a history of VVS have suggested that not just the pooled volume, but also the rate by which the hypovolemic stimulus is instituted can affect the responses to orthostatic stress (27,77). Despite a similar capacitance response, Lindenberger and Länne (77) found a much slower lower limb blood pooling in otherwise healthy women experiencing vasovagal reactions during moderate levels of LBNP compared to hemodynamic stable women.…”
Section: Pathophysiology Of Vasovagal Syncopementioning
confidence: 99%
See 3 more Smart Citations